Use of Noninvasive Ventilation with Volume-assured Pressure Support for Treatment-refractory Myasthenia Gravis - Diaz-Abad, Montserrat (Innov Clin Neurosci, 2019)
Background: Stepwise approach to therapy and increasing use of immunosuppressive agents have led to increasingly good prognosis and survival in myasthenia gravis (MG). However, there is a small subset of patients with treatment-refractory disease who experience a higher disease burden and increased rates of myasthenic crises and exacerbations, including respiratory failure. A 54-year-old man with treatment-refractory MG on chronic plasma exchange therapy had rapidly fluctuating weakness, poor sleep quality, and worsening respiratory symptoms in between treatments. He was started on home nocturnal noninvasive ventilation with volume-assured pressure support mode and experienced marked improvement in sleep quality, dyspnea, fatigue, and daytime sleepiness.